1991
DOI: 10.1007/bf01400492
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of cerebrovascular diseases

Abstract: The seasonal variation in all admissions of all types of cerebrovascular disease within the West Midlands Region was examined between the years 1973-1980. There was a fluctuation for both sexes with a peak in winter, between the months of October and April; a trough was observed in late summer, in July and August. Multivariate analysis of the meteorological factors showed an association between hours of sunshine and intracerebral haemorrhage. The meterological variables were strongly correlated with each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 8 publications
6
23
0
Order By: Relevance
“…2,12,14,17,22,27,[29][30][31] The highest occurrences of SAH were found in spring in women and in late fall in men, 4) in spring and fall in men, and in winter in women, 24) and in winter in women and no peak in men. 32) Our data resembled the results of 10 years of the Canadian Collaborative Study Group although the lowest occurrence in their male group was in summer whereas that of in the present study was in winter. 24) This inconsistency and inconclusiveness can be explained by differences in study, hospital-based studies versus population-based studies, by differences in environmental conditions and lifestyle between the countries, 5) and by relatively small numbers of events available for analysis.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…2,12,14,17,22,27,[29][30][31] The highest occurrences of SAH were found in spring in women and in late fall in men, 4) in spring and fall in men, and in winter in women, 24) and in winter in women and no peak in men. 32) Our data resembled the results of 10 years of the Canadian Collaborative Study Group although the lowest occurrence in their male group was in summer whereas that of in the present study was in winter. 24) This inconsistency and inconclusiveness can be explained by differences in study, hospital-based studies versus population-based studies, by differences in environmental conditions and lifestyle between the countries, 5) and by relatively small numbers of events available for analysis.…”
Section: Discussionsupporting
confidence: 71%
“…2,4,6,11,12,14,15,17,18,20,22,24,26,27,[29][30][31][32][33] Hospital-based and populationbased studies that demonstrated significant seasonal variation found that the peak period for SAH differed widely. [4][5][6]15,20,24,26,32,33) No statistically significant seasonal variations were also observed in some studies. 2,12,14,17,22,27,[29][30][31] The highest occurrences of SAH were found in spring in women and in late fall in men, 4) in spring and fall in men, and in winter in women, 24) and in winter in women and no peak in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous multivariate analysis of various climate factors found that shorter sunshine duration was significantly associated with occurrence of SAH and showed the lowest p value. 13) Although we did not perform multivariate analysis due to the strong mutual association of many climate factors, 26) the amount of global solar radiation was smaller on the onset days with the lowest p value in our study as well (Table 4).…”
Section: Discussionmentioning
confidence: 65%
“…Seasonal variation and meteorological association of stroke has long been controversial, but only a small number of studies have focused specifically on SAH, so whether such epidemiological phenomena exist has not been determined. Statistically significant seasonal or circannual cyclic trends have been reported [2][3][4]7,12,13,19,26,27) and some meteorological factors were significantly associated with the occurrence of SAH. 2,4,7,13,15) However, other studies have not found significant seasonal variation or meteorological association.…”
Section: Introductionmentioning
confidence: 99%